It all adds up …. Or does it? Numbers, mathematics and purpose. (August 2016) - Conway Morris, Simon
Abstract: No chimpanzee knows what a square root is, let alone a complex number. Yet not only our closest ape cousins but even some invertebrates, possess a capacity for numerosity, that is the ability to assess relative numerical magnitudes and distances. That numerosity should confer adaptive advantages, such as social species that choose shoal size, is obvious. Moreover, it is widely assumed that numerosity and mathematics are seamlessly linked, as would be consistent with Darwinian notions of descent and modification. Animal numerosity, however, involves sensory processes (usually vision, but other modalities such as olfaction can be as effective) that follow psychophysical principles, notable the Weber-Fechner law. In contrast, mathematics may require sensory mediation but is an abstract process. The supposed connection between these processes is described as supramodality but the mechanisms that allow humans, but not animals, to engage in even simple mathematics are opaque. Here, I argue that any resolution will depend on proper explanations for not only mathematics, but language and by implication consciousness. In this light, concepts of purpose are not intellectual mirages but legitimate descriptions of the worlds in which we are embedded. These are both visible (and tangible) and invisible (and although intangible, equally real). Highlights: Animal (and human) numerosity is demonstrably a sensory process, following the Weber-Fechner law. Mathematics is taken to be a supervenience of numerosity, but this is an unwarranted extrapolation. Mathematics is an abstract process, is mediated by language, and is uniquely human. Connections, or lack thereof, between numerosity and mathematics are a test-case for consciousness.